Comparison of the Number of Staphylococcus aureus Colonies in Green Grass Jelly (Cyclea barbata Miers) and Black Grass Jelly (Mesona palustris) Sold in the Lubuk Pakam Area - Selda manullang; Yemima Sundita Damanik; Sa’adah Siregar (Institut Kesehatan Medistra Lubuk Pakam, 2026)
Food contamination by pathogenic bacteria is a public health problem that can cause digestive disorders and even serious infections. One of the bacteria commonly found in food is Staphylococcus aureus, which is capable of producing enterotoxins and causing food poisoning. Green grass jelly (Cyclea barbata Miers) and black grass jelly (Mesona palustris) are traditional food products widely consumed by the community and are generally produced and sold in a traditional manner, increasing the risk of bacterial contamination due to poor hygiene practices. This study aimed to compare the number of Staphylococcus aureus colonies in green grass jelly and black grass jelly sold in the Lubuk Pakam area. This research used a laboratory experimental method with a streaking technique on Mannitol Salt Agar (MSA) media using a sterile inoculating loop. Samples were inoculated onto the media and incubated to allow colony growth. Bacterial identification was carried out through macroscopic observation, Gram staining, and biochemical tests including catalase and coagulase tests. The results showed that all samples of green and black grass jelly were positive for Staphylococcus aureus. The total number of colonies in green grass jelly was 465 colonies with an average of 116.25 colonies, while black grass jelly showed a total of 880 colonies with an average of 220 colonies. The difference in the average colony count between the two samples was 103.75 colonies, indicating that black grass jelly had a higher level of contamination than green grass jelly. In conclusion, there is a difference